2017
DOI: 10.3390/ijfs5040025
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the Number of Social Media Fans for North American and European Professional Sports Clubs with Determinants of Their Financial Value

Abstract: Abstract:The aim of this article is to investigate the explanatory variables of the number of Facebook fans and Twitter followers for professional sports clubs based on the financial value literature. Such explanatory variables are related to local market conditions and on-field and off-field performance. Based upon a sample of North American major league clubs and the most valuable European soccer clubs as evaluated by Forbes over the 2011-2013 period (423 observations), our results indicate a range of variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(61 reference statements)
0
13
0
2
Order By: Relevance
“…The sport is characterized as being one of the most popular sports worldwide according to the number of people participating, particularly in continents such as Europe and South America. It attracts a large number of followers due to the combination of simple technical movements, which provoke strong emotional responses in spectators [6,7]. In addition, it is worth noting that football is becoming a great attraction for new generations in continents such as North America and Asia, where it is growing in popularity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The sport is characterized as being one of the most popular sports worldwide according to the number of people participating, particularly in continents such as Europe and South America. It attracts a large number of followers due to the combination of simple technical movements, which provoke strong emotional responses in spectators [6,7]. In addition, it is worth noting that football is becoming a great attraction for new generations in continents such as North America and Asia, where it is growing in popularity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, club identification and the win/lose phenomenon are the most considerable influences on the satisfaction of spectators (Byon, Zhang, & Baker, 2013;Scelles et al, 2017). Thus, increasing the understanding of the determinants of winning or losing is of major importance for football clubs.…”
Section: Introductionmentioning
confidence: 99%
“…It is often seen in the literature that sports clubs are generally evaluated in terms of financial and sportive performance through the football branch. Besides, it was stated that there is a relationship between the sportive success of sports clubs and their market values (Barajas, Castro-Limeres and Gasparetto, 2017;Ergül, 2017;Ferri, Macchioni, Maffei and Zampella, 2017;Galariotis, Germain and Zopounidis, 2018;Guzman and Morrow, 2007;Sakınç, Açıkalın and Soygüden, 2017;Scelles, Helleu, Durand, Bonnal and Morrow, 2017;Uluyol, 2014;Zambom-Ferraresi, Lera-López and Iráizoz, 2017). In a few studies, it has been observed that evaluations of another branch other than football or the effectiveness of sports clubs were examined (Erturan Öğüt and İmamoğlu, 2011;Eskicioğlu, Doğu, and Özsoy, 2012).…”
Section: Literaturementioning
confidence: 99%